Can top-down and bottom-up forces explain phytoplankton structure in a subtropical and shallow groundwater-connected lake? - Frau, Diego (2015)
Bottom-up and top-down control of phytoplankton is one of the most important hypothesis that explains and predicts the structure of aquatic community. Our aim was to elucidate whether predation and resource limitation can control phytoplankton composition and abundance in a subtropical shallow lake with groundwater connection to the river system. During 12 months, the lake was sampled at three points. Physico-chemical parameters, phytoplankton and zooplankton were sampled fortnightly, whereas fish were sampled every 3 months. The results showed that Euglenophyta dominated the total biovolume, followed by Dinophyta and Cryptophyta. As for the species composition, Chlorophyta was the dominant group (80 species recorded), followed by phylum Cyanobacteria (26 species recorded). Redundancy analysis (RDA) indicated that temperature and nitrate + nitrite concentration mainly explained biovolume changes, with zooplankton predation not having any measurable effect on phytoplankton during the high-water (HW) period. During low-water (LW) period top-down by fish was more important. At higher taxonomic resolution (species biovolume), phosphorus was another controlling factor. We concluded that phytoplankton in this lake is mainly regulated by hydrological changes as a macrofactor that affects nutrient availability and other environmental conditions. Even though bottom-up top-down forces do not have a central effect, we found evidence of positive nutrient influences at the HW period and fish effect at the LW period.